Control of acoustic tone formation using shape geometry modifications and jet blowing in a cavity experiencing supersonic flow - Olanrewaju M. Oyewola; Morakinyo J. Labiran (International Journal of Thermofluids)
Acoustics tones have caused significant damage to sensitive electronic equipment and aircraft respectively. The effects become severe in cavities experiencing turbulent flows and could lead to human fatalities. Studies have compared the effects of cover plate (CP) and jet-blowing (JB) systems in suppressing the propagation of these undesirable effects. The sound pressure levels (SPL) were observed to decrease by 10 % and 3 % in the former and latter respectively. This study critically examines the combined effect of CP geometry modifications, jet orifice positions as well as integration with other established flow control techniques (FCT) with the possibility of achieving further attenuation in the system. Geometric sizes of the CP are set to 20 %, 25 % and 30 % of the cavity length, with a length-to-depth ratio (l/d) of 5.07 and simulated in a flow field with a Mach number of 1.5. Also, four orifices for jet blowing are varied on the cavity leading and trailing edge wall. The trailing edge modification and trailing edge curvature are also implemented on the cavity. The k-ꙍ turbulence model and second-order discretization method are used to perform the computation. Results show that the trailing edge region produced the largest pressure fluctuations. Also, it was observed that longer cover plates (0.3l) permit the formation of self-oscillating frequencies as the flow field is brought closer to the trailing edge. However, the further inclination of the trailing wall will ensure prompt evacuation and dissipation of the flow turbulence energy. At the trailing edge, the jet-blowing control technique successfully attenuated approximately 10 dB in SPL, though a significant amount of turbulence was introduced into the system. Overall, the trailing edge modification, inclined cover plate with a 0.25l and jet blowing on the trailing and leading edges produced an approximate 27.5 % reduction in acoustic tone suppression.